2010
DOI: 10.1177/0333102410388437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of red ear syndrome in juvenile primary headaches

Abstract: Our study showed that (i) in children, RES is a highly specific sign for migraine. In addition, the evidence of an association of RES with some migraine features partially provoked by the parasympathetic system supports the hypothesis of a shared pathophysiological background (e.g. via the activation of the trigeminal-autonomic reflex).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…It is interesting that in our patient's case, the migraine without aura occurred about one year later after RES and usually migraine and RES appeared simultaneously on the same side of head. This coexistence was proved by Raieli, who showed in her study that in the pediatric age group the RES is a rather frequent clinical sign during headache and is more frequent during migraine [7]. It should be noted that the symptoms of RES do not have to be associated with a headache.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is interesting that in our patient's case, the migraine without aura occurred about one year later after RES and usually migraine and RES appeared simultaneously on the same side of head. This coexistence was proved by Raieli, who showed in her study that in the pediatric age group the RES is a rather frequent clinical sign during headache and is more frequent during migraine [7]. It should be noted that the symptoms of RES do not have to be associated with a headache.…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of RES is also unknown, although it is thought that idiopathic RES is more common in children, while the secondary RES is probably more frequent in adults [6]. There are some articles that draw attention toward RES being associated with primary headache disorders, including migraine, chronic paroxysmal hemicranias (CPH), hemicrania continua (HC) and shortlasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) [7,8]. It is interesting that in our patient's case, the migraine without aura occurred about one year later after RES and usually migraine and RES appeared simultaneously on the same side of head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association with primary headache diseases supports the suspicion of pathogenesis with activation of the trigeminal-autonomic reflex and places RES close to an exclusively neurological disease with secondary functional impairment of the microhemovascular system of the ear skin. Raieli et al [9] suggested a shared pathophysiological background because of the association of RES with some migraine features partially provoked by the parasympathetic system. In secondary RES, by contrast, local factors or irritation of the third cervical root are assumed, which lead to the typical symptoms via a release of vasoactive peptides such as substance P or calcitonin-gene-related peptide and nitric oxide [2].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of migraine in Tourette syndrome subjects was nearly fourfold more than the general population [68] . A migraine is associated with motion sickness, recurrent limb pain, and red ear syndrome, characterized by intermittent unilateral ear pain or burning with redness of that ear that may be associated with headache [69] .…”
Section: Co-morbiditiesmentioning
confidence: 99%